2016
DOI: 10.1096/fj.201500048
|View full text |Cite
|
Sign up to set email alerts
|

S‐glutathiolation impairs phosphoregulation and function of cardiac myosin‐binding protein C in human heart failure

Abstract: Cardiac myosin-binding protein C (cMyBP-C) regulates actin-myosin interaction and thereby cardiac myocyte contraction and relaxation. This physiologic function is regulated by cMyBP-C phosphorylation. In our study, reduced site-specific cMyBP-C phosphorylation coincided with increased S-glutathiolation in ventricular tissue from patients with dilated or ischemic cardiomyopathy compared to nonfailing donors. We used redox proteomics, to identify constitutive and disease-specific Sglutathiolation sites in cMyBP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…PKGIα activity was expressed as pmol phosphate incorporated into PKGIα substrate per minute. On the other hand, activity of human WT, Cys42Ser, Cys117/195Ser, or Cys42/117/195Ser PKGIα was assessed by phosphorylation of recombinantly expressed His 6 -tagged cardiac myosin-binding protein C (amino acid residues 153-450) 41 , which was previously described as a PKGIα substrate 42 , in the presence of radiolabeled γ 32 P-ATP (GE Healthcare). HEK-293 cells were transfected as described before and exposed to AS (500 µmol/L, 15 min), NCA (100 µmol/L, 30 min) or vehicle (NaOH for AS; DMSO for NCA).…”
Section: Methodsmentioning
confidence: 99%
“…PKGIα activity was expressed as pmol phosphate incorporated into PKGIα substrate per minute. On the other hand, activity of human WT, Cys42Ser, Cys117/195Ser, or Cys42/117/195Ser PKGIα was assessed by phosphorylation of recombinantly expressed His 6 -tagged cardiac myosin-binding protein C (amino acid residues 153-450) 41 , which was previously described as a PKGIα substrate 42 , in the presence of radiolabeled γ 32 P-ATP (GE Healthcare). HEK-293 cells were transfected as described before and exposed to AS (500 µmol/L, 15 min), NCA (100 µmol/L, 30 min) or vehicle (NaOH for AS; DMSO for NCA).…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, S-glutathionylation itself could prevent phosphorylations on specific sites. Previous publications showed that several cysteines of cMyBP-C can be S-glutathionylated in vitro [15,16].…”
Section: Cardiac Stress Intensity and Functionmentioning
confidence: 99%
“…Stathopoulou et al [16] showed that in vitro S-glutathionylation of Cys249, localized near the phosphorylation sites, attenuated phosphorylations by protein kinases (PKA and CaMKII). This may explain why after HSE, PKA-mediated phosphorylation of TnI and cMyBP-C was similar in control and HSE hearts despite higher PKA activity ( Fig.…”
Section: Cardiac Stress Intensity and Functionmentioning
confidence: 99%
See 2 more Smart Citations